PERANCANGAN PROMOSI POTENSI WISATA ALAM KABUPATEN LIMA PULUH KOTA DENGAN MEDIA VIDEO TRAVELING - MUHAMMAD HANAFI, Dra. Jupriani, M.Sn, Riri Trinanda, S.Pd., M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2015)
Indonesia has a lot of tours, especially the wealth of natural attractions. Nowadays, the tourism sector as economic activity has become a mainstay and a priority for the development of every region in Indonesia. Lima Puluh Kota regency have quite diverse natural resources such as lakes, rivers, waterfalls, canyons, forests and so on. Natural potential that is the income for the inhabitants and government of Lima Puluh Kota regency. But there are still many natural resources in Lima Puluh Kota regency that have potential but have not run into attractions such as Lubuak Batu Bulan Kubang Balambak waterfalls, Sialang Indah Situjuh waterfalls and Lokuak Singkuang Halaban waterfalls. Seeing these conditions, designers interested in creating a draft promotional videos and media traveling supporters natural tourist potential in the Lima Puluh Kota regency.Keywords : Promotion, tourism, video traveling